Acute Psychosis Associated with Subcortical Stroke: Comparison between Basal Ganglia and Mid-Brain Lesions. (17th September 2014) - McMurtray, Aaron; Tseng, Ben; Diaz, Natalie; Chung, Julia; Mehta, Bijal; Saito, Erin
Abstract : Acute onset of psychosis in an older or elderly individual without history of previous psychiatric disorders should prompt a thorough workup for neurologic causes of psychiatric symptoms. This report compares and contrasts clinical features of new onset of psychotic symptoms between two patients, one with an acute basal ganglia hemorrhagic stroke and another with an acute mid-brain ischemic stroke. Delusions and hallucinations due to basal ganglia lesions are theorized to develop as a result of frontal lobe dysfunction causing impairment of reality checking pathways in the brain, while visual hallucinations due to mid-brain lesions are theorized to develop due to dysregulation of inhibitory control of the ponto-geniculate-occipital system. Psychotic symptoms occurring due to stroke demonstrate varied clinical characteristics that depend on the location of the stroke within the brain. Treatment with antipsychotic medications may provide symptomatic relief.